Differences in Physical and Psychological Parameters in Sub-Elite, Male, Youth Soccer Players with Jumper's Knee Following Physical Therapy Compared to Healthy Controls: A Longitudinal Examination - Marc Niering; Thomas Muehlbauer (North American Sports Medicine Institute, 2021)
# Purpose/Background Many adolescent athletes suffer from jumper's knee (JK) over a long period of time and return to sports before symptoms are fully resolved. Current treatment methods may not reduce pain in the short term, especially not during a competitive season. The purpose of this study was to investigate differences in physical, psychological, and injury-/pain-related parameters in sub-elite male youth soccer players, who previously underwent physical therapy for JK compared to healthy controls (HC) over the course of a season. # Methods All subjects were tested four times (start of the season \[T1\], 6 \[T2\], 16 \[T3\], and 20 \[T4\] weeks after the start of the season). Outcome measures included muscle power (drop jump, jump-and-reach), change of direction speed \[CODS\] (acyclic sprint), speed (tapping, 30-m linear sprint), endurance (Yo-Yo intermittent recovery test level 1), the Achievement Motives Scale (AMS) Sport, and injury-/pain-related data. Univariate analysis of variance was used to compare differences in variables between the two groups over the course of a soccer season. # Results Over the season, the jumper's knee group (JK; 15.1 ± 0.8 yr) demonstrated significantly worse physical performance in CODS (to the left side: 1.37≤ Cohen's *d* ≤ 1.51 \[T1-T4\]; *p* \< 0.001 / to the right side: 1.24 ≤ *d* ≤ 1.53 \[T1-T4\]; *p* \< 0.001) and speed (0.48 ≤ *d* ≤ 1.26 \[T1-T4\]; *p* \< 0.007) compared to healthy controls (HC; 15.0 ± 1.0 yr). Further, psychological parameters showed worse values in JK than in HC for the AMS Sport items "hope for success" and "fear of failure" that especially showed a significant difference at T1 (*d* = 0.65; *p* = 0.032 / *d* = 0.68; *p* = 0.027) and T2 (*d* = 0.50; *p* = 0.076 / *d* = 0.80; *p* = 0.012). Moreover, the JK group showed significantly higher incident rates for non-contact lower limb injuries (*d* = 0.69; *p* = 0.049) per 1,000 hours (i.e., practices/competitions), injury-related rest periods (*d* = 2.06; *p* = 0.043), and pain-related training interruptions (*d* = 1.35; *p* \< 0.001). # Conclusions The observed findings imply that there are significant differences in physical and psychological performance of youth soccer players after physical therapy for JK compared to HC. When designing rehabilitation and/or training programs, as well as determining the point of return to sport the impact of the injury needs to be taken into account. # Level of Evidence: 1b